2020
DOI: 10.1093/ajcp/aqaa066
|View full text |Cite
|
Sign up to set email alerts
|

Engrailed Homeobox 1 and Cytokeratin 19 Are Independent Diagnostic Markers of Eccrine Porocarcinoma and Distinguish It From Squamous Cell Carcinoma

Abstract: Objectives The diagnostic utility of En1 in the histopathologic differentiation of eccrine porocarcinoma (EPC) from invasive squamous cell carcinoma (SCC) was investigated. Methods Expression of En1 and CK19 in 16 cases of EPC was immunohistochemically examined and compared with that in 32 cases of SCC. Results In all 16 EPCs, En1 was expressed in 3% to 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Among the adult organs, En1 is expressed only in the eccrine gland, 12 contrary to its expression in the embryonic brain 29 and epidermis of the ventral limb 10 . In tumor tissues, En1 is occasionally expressed in cutaneous squamous cell carcinoma 12,30 and triple‐negative breast carcinoma 31 occurs in the organs other than the salivary glands and eccrine glands. According to the open database resource of Human Protein Atlas, 32 En1 expression was found in 15 of 207 tumor cases occurring in 20 organs, and only four of them were En1‐positive based on our criteria, which showed En1 expression in more than 25% of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the adult organs, En1 is expressed only in the eccrine gland, 12 contrary to its expression in the embryonic brain 29 and epidermis of the ventral limb 10 . In tumor tissues, En1 is occasionally expressed in cutaneous squamous cell carcinoma 12,30 and triple‐negative breast carcinoma 31 occurs in the organs other than the salivary glands and eccrine glands. According to the open database resource of Human Protein Atlas, 32 En1 expression was found in 15 of 207 tumor cases occurring in 20 organs, and only four of them were En1‐positive based on our criteria, which showed En1 expression in more than 25% of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the distinction between porocarcinoma, the malignant counterpart of poroma, and poorly differentiated squamous cell carcinoma can be a diagnostic challenge in current practice. 7 In this context, several immunohistochemical markers have been proposed to distinguish benign and malignant poroid tumors from their differential diagnoses. Indeed, epithelial membrane antigen is expressed in poroma cells, and carcinoembryonic antigen highlights the ductal structures.…”
mentioning
confidence: 99%
“…Accordingly, a wide range of epidermal and adnexal neoplasms have to be considered in the differential diagnoses. Moreover, the distinction between porocarcinoma, the malignant counterpart of poroma, and poorly differentiated squamous cell carcinoma can be a diagnostic challenge in current practice 7…”
mentioning
confidence: 99%
“…The morphology of porocarcinomas can be variable, with the squamoid variant posing a particular challenge to differentiate from invasive squamous cell carcinoma, as reflected in our case. [7][8][9][10] However, it is imperative to make this histologic distinction because porocarcinomas have been shown to have a higher risk of local recurrence, lymph node metastasis, systemic metastasis, and overall mortality compared with squamous cell carcinoma. 7 Helpful histologic clues that distinguish this tumor from squamous cell carcinoma include the prominent anastomosing cords and the identification of a coexisting poroma component.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 94% of porocarcinomas in 1 study were found to express both engrailed homeobox 1 (En1) and CK19, compared with the lack of combined expression in any of the squamous cell carcinomas examined. 9 CD117 (C-kit) has also been shown to be useful in separating squamous cell carcinoma from porocarcinoma because most porocarcinomas should express CD117, at least focally, while only a minority of squamous cell carcinomas express CD117 (∼20%). 11…”
Section: Discussionmentioning
confidence: 99%